Image, Science and Technology: a Post-phenomenological Approach. Entrevista com Don Ihde - Wellner, Galit (Prometeica - Revista de Filosofía y Ciencias, 2018)
Image, Science and Technology: a Post-phenomenological Approach. Entrevista com Don Ihde